Sustainability and optimization methods under uncertainties in closed-loop supply chain. (September 2022) - Li, Lu; Liao, Haolan; Zhou, Jizhi; Wang, Yuhan
Abstract: Due to the environment-friendly attribution and cost-saving potential of remanufacture, many original equipment manufacturers (OEMs) commence taking it as part of production strategy. While the inherent uncertainties in closed-loop supply chain (CLSC) add to the difficulty in operational management. As the first case on the coupling effect of multi-uncertainties, the paper carries out analyses of eight critical uncertainties and quantifies the impacts on the whole CLSC. Based on mathematical derivation and followed by numerical experiments, the results demonstrate that by formulating appropriate remanufacture-up-to ratio, OEMs are able to adjust the relationship between supply and demand indirectly, and then strike an optimal balance to maximize the economic benefits under multi-uncertainties. The conclusion drew from this study provides a scientific support for practitioners to develop production strategies for optimal material efficiency and sustainable industrial development in CLSC. Highlights: Establish correlation between uncertain quality and economic indexes. Make comparative analysis of the impacts of different scenarios on CLSC. Quantify the coupling effect of different uncertainties in CLSC. Present the optimal production strategy under multiple uncertainties.